Characterization of a novel staphylococcal cassette chromosome composite island from community-associated MRSA isolated in aged care facilities in Western Australia - Wilson, L.; Coombs, Geoffrey; Christiansen, K.; Grubb, Warren; O'Brien, Frances (2016)
BACKGROUND: In Western Australia (WA), clonal complex 5, ST835, community-associated (CA) MRSA is isolated almost exclusively from aged care facilities. In WA four different staphylococcal cassette chromosome (SCC) mec (SCCmec) elements have been identified in this ST, indicating high genetic activity in the SCCmec region. OBJECTIVES: To investigate the SCC region of ST835 CA-MRSA WA MRSA-40 and determine the distribution of an SCCsorbitol element found within the region. RESULTS: The SCC region contained a composite island, SCCmecWA MRSA-40-CI, that was composed of three elements, ?SCCpls, SCCsorbitol and SCCmecVT (5C2 & 5). This is the first time that a sorbitol operon has been reported in an SCC element. CONCLUSIONS: Generation of SCCmecWA MRSA-40-CI has involved multiple genetic events and recombination with CoNS has occurred during evolution of the SCC elements. While Staphylococcus aureus is renowned for its ability to utilize mobile genetic elements to disseminate antimicrobial resistance, the SCC region of WA MRSA-40 shows that this clone has also utilized SCC elements to acquire extra virulence and possibly adapt to a niche environment.